Sociodemographic correlates, job satisfaction, and burnout among special education teachers - Hala Abd Ellatif Elsayed; Ghaida Almoabadi; Maram Albeshri (Acta Psychologica)
Background: Special education teachers are at heightened risk of job-related stress and burnout due to the emotional demands of working with students who have disabilities. In Saudi Arabia, the growing number of students with psychological comorbidities adds further complexity to the educational environment. However, limited research has addressed how teachers' sociodemographic characteristics and comorbid conditions among students affect their psychological well-being and job satisfaction. Objectives: This study aimed to examine the relationships between sociodemographic variables (gender, age, marital status, education level, years of experience), job satisfaction, and the three dimensions of burnout (emotional exhaustion, depersonalization, and personal accomplishment) among special education teachers in Saudi Arabia. It also investigated whether teaching students with psychological comorbidities moderates these relationships. Methods: A cross-sectional, correlational design was employed. 393 special education teachers from different regions of Saudi Arabia participated in the study. Data were collected using validated Arabic versions of the Maslach Burnout Inventory and the Satisfaction with Work Scale. Additionally, teachers indicated whether they worked with students diagnosed with more than one psychological disorder (e.g., autism, ADHD, anxiety). Descriptive statistics, Pearson correlation, and two-way ANOVA were used for data analysis. Results: The study found moderate emotional exhaustion (M = 25.36), high depersonalization (M = 12.35), and low personal accomplishment (M = 28.52) among participants. Job satisfaction was rated as satisfactory (M = 16.31). Significant associations emerged between education level and job satisfaction (r = −0.147, p < 0.01) and between years of experience and job satisfaction (r = 0.112, p < 0.05). Burnout levels were significantly affected by gender, education level, and years of experience, with notable interaction effects from the presence of psychological comorbidities (e.g., F (3,385) = 9.23 for education level on emotional exhaustion; F (1,389) = 17.98 for sex on depersonalization, p < 0.001). Conclusions: The findings highlight the complex interplay between teacher characteristics and student profiles in shaping occupational well-being. Teachers with higher academic qualifications and those working with students with multiple psychological disorders exhibited higher emotional exhaustion and depersonalization. These results underscore the need for targeted support, mental health interventions, and policies aimed at improving working conditions for special education teachers in Saudi Arabia. The study addresses a significant gap in the regional literature and aligns with national goals to improve inclusive education quality.